Familias tejedoras de futuro Propuesta de investigación-intervención en contextos de posconflicto y paz - Arroyave Gómez, Martha Cecilia (Universidad Católica Luis Amigó, 2021)
The process of carrying out a research and intervention proposal with a community and families in the municipality of Granada, specifically in the Bello Horizonte sector, has a background related to the history and positioning of a group of professionals and practitioners who, during the recent years, with the support of institutions and the University of Antioquia, have been carrying out social interventions in different sectors of the municipality, both rural and urban, with different populations: women, children, young people, constituting "a psychosocial team." In this specific proposal, fabrics were generated from their past and present experiences, having as a priority the community's participation, possibilities, and strengths, giving rise to this construction.